Effect of temperature on photophysical properties of polymeric nanofiber materials with porphyrin photosensitizers - Suchánek, Jan; Henke, Petr; Mosinger, Jiří; Zelinger, Zdeněk; Kubát, Pavel (The journal of physical chemistry. B, 2014)
Electrospun nanofibers possess large surface to volume ratios, high porosity, and good mechanical properties that are necessary for biological applications. We prepared different types of photoactive polymeric nanofiber materials with encapsulated or externally bound porphyrin photosensitizers. The kinetics of formation and the decay of both singlet oxygen O2((1)Δg) and porphyrin triplet states that are generated by irradiation of nanofiber materials in an air atmosphere or in an air-saturated aqueous solution were measured and evaluated by luminescence and transient absorption spectroscopy in the temperature range between 5 and 60 °C. We found shortening of the O2((1)Δg) lifetime and a significant increase in singlet oxygen-sensitized delayed fluorescence at higher temperatures. These photophysical data show an increase in the diffusion coefficient for O2((1)Δg) with temperature, and they are consistent with a stronger antibacterial effect of the nanofiber material on Escherichia coli at higher temperature.
Keywords: fotosenzibilizující látky; světlo; Temperature; Photosensitizing Agents; teplota; singletový kyslík; Microscopy, Electron, Scanning; Escherichia coli; vzduch; Nanofibers; antibakteriální látky; spektrální analýza; Air; Light; polymery; difuze; Kinetics; Polymers; Porphyrins; nanovlákna; Anti-Bacterial Agents; Diffusion; mikroskopie elektronová rastrovací; voda; Spectrum Analysis; porfyriny; Water; Singlet Oxygen; kinetika